Key management scheme with private key self-healing ability in DTN - De-quan LI; Xi-yong ZHANG; Ting-ting ZHANG; Guan-jun GUO (网络与信息安全学报)
Because of the large delay of DTN network,node cannot receive broadcast updating private key messages in a timely manner,thus unable to update the private key for a certain time period.Aiming at this problem,an allowing private key self-healing clustering key was management scheme.The scheme can not only accomplish the distribution of the private keys of node and update,but also can self-heal the old time private keys.Security and efficiency analysis show that the scheme is particularly suitable for large network latency,intermittent connection DTN network.